High performance Na3V2(PO4)3 cathode prepared by a facile solution evaporation method for sodium-ion batteries. Issue 6 (15th April 2017) - Zheng, Li-Li; Xue, Yuan; Liu, Bao-Sheng; Zhou, Yu-Xiang; Hao, Su-E.; Wang, Zhen-bo
Abstract: Based on its abundance and low cost, sodium based batteries have aroused extensive attention for large scale energy-storage systems. In the current work, Na3 V2 (PO4 )3 prepared by a facile solution evaporation method (denoted as NVP-SE) is used as cathode materials for sodium ion battery, with a control sample by solid state method. Raman spectrum and TEM are used to study the carbon layer coated on NVP-SE. The results show a highly graphitization and well-coated carbon layer, which is predominant by sp 2 carbon. Graphitized carbon leads to high electrical conductivity, which can improve the rate performance of Na3 V2 (PO4 )3 materials. Besides, GITT tests show high Na-ion diffusion coefficient. Even at 30 C, the NVP-SE cathode still delivers a capacity of 70 mAh g −1 . Moreover, the material also shows great long term cycling performance. After 500 cycles at 1 C rate and 1000 cycles at 5 C, its discharge capacities are still 103.3 mAh g −1 and 85.4 mAh g −1, which maintain 92.6% and 85.0% of its initial capacity. Thus, simple preparation process and excellent electrochemical performance for Na3 V2 (PO4 )3 /C extend it as a potential material for high power applications.